DNA Methylation at Birth is Associated with Childhood Serum Immunoglobulin E Levels - Han, Luhang (Epigenet Insights, 2021)
Immunoglobulin E (IgE) is known to play an important role in allergic diseases. Epigenetic traits acquired due to modification of deoxyribonucleic acid (DNA) methylation (DNAm) in early life may have phenotypic consequences through their role in transcriptional regulation with relevance to the developmental origins of diseases including allergy. However, epigenome-scale studies on the longitudinal association of cord blood DNAm with IgE over time are lacking. Our study aimed to examine the association of DNAm at birth with childhood serum IgE levels during early life. Genome-scale DNAm and total serum IgE measured at birth, 5, 8, and 11 years of children in the Taiwan Maternal and Infant Cohort Study were included in the study in the discovery stage. Linear mixed models were implemented to assess the association between cord blood DNAm at ~310K 5′-cytosine-phosphate-guanine-3′ (CpG) sites with repeated IgE measurements, adjusting for cord blood IgE. Identified statistically significant CpGs (at a false discovery rate, FDR, of 0.05) were further tested in an independent replication cohort, the Isle of Wight (IoW) birth cohort. We mapped replicated CpGs to genes and conducted gene ontology analysis using ToppFun to identify significantly enriched pathways and biological processes of the genes. Cord blood DNAm of 273 CpG sites were significantly (FDR = 0.05) associated with IgE levels longitudinally. Among the identified CpGs available in both cohorts (184 CpGs), 92 CpGs (50%) were replicated in the IoW in terms of consistency in direction of associations between DNA methylation and IgE levels later in life, and 16 of the 92 CpGs showed statistically significant associations (P < .05). Gene ontology analysis identified 4 pathways (FDR = 0.05). The identified 16 CpG sites had the potential to serve as epigenetic markers associated with later IgE production, beneficial to allergic disease prevention and intervention.